MAIN ASPECTS OF ETHICAL STANDARDS DEVELOPMENT IN THE FIELD OF MEDICAL AND PHARMACEUTICAL EDUCATION - Zakharchuk , Oleksandr; Horoshko , Oleksandra; Matushchak , Marta; Ezhned , Mariia; Sakhatska , Inna; Drachuk , Vira (Collection of scientific papers «ΛΌГOΣ», 2023)
The activity of a doctor and pharmacist is aimed at preserving the patient's health, therefore, requires a specialist to treat a person humanely, respect for his or her personality, goodwill, complicity, tolerance and justice. Studying the basic principles of ethics and deontology while studying at the university will allow you to apply your knowledge in practice, which will ensure the inadmissibility of errors in work, teach you to control yourself, and orient you to a constant striving to improve your knowledge of medicine and pharmacy. Adherence to the norms and principles set forth in the Code will help to establish a constructive dialog between a doctor, pharmacist and patient.